Self-management of osteoarthritis while waiting for total knee arthroplasty during the COVID-19 pandemic among older Malaysians - Mahdzir, Ahmad Nabil Khairi; Mat, Sumaiyah; Seow, Shi Rui; Abdul Rani, Rizal; Che Hasan, Muhammad Kamil; Mohamad Yahaya, Nor Hamdan (Baishideng Publishing, 2023)
BACKGROUND The study sought to understand the self-management strategies used by patients during the postponement of their total knee arthroplasty (TKA) procedure, as well as the associations between the length of waiting time, pain, and physical frailty and function. The study focused on individuals aged 50 years and above, as they are known to be more vulnerable to the negative impacts of delayed elective surgery and rehabilitation. This study hypothesizes that delayed TKR due to coronavirus disease 2019 (COVID-19) will bear negative effect in self-management, pain, and physical frailty and function in older adults.